A multinational examination of the symbolic–instrumental framework of consumer–brand identification - Lam, Son K; Ahearne, Michael; Schillewaert, Niels (Journal of International Business Studies, 2012)
The authors propose a symbolic–instrumental interactive framework of consumer–brand identification (CBI) and explore its predictiveness across 15 countries. Using multinational data, they show that the negative impact of the misalignment between self–brand congruity and perceived quality on CBI is universal. The interaction among CBI, perceived quality, and uncertainty avoidance orientation in motivating consumers’ identity-sustaining behavior is weak. However, the synergy between CBI and perceived quality in motivating consumers’ identity-promoting behavior is stronger among collectivist consumers. The authors derive a typology of symbolic–instrumental misalignments to help international marketing managers motivate consumers to identify with and promote brands.